2004
DOI: 10.1021/cm035079w
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Dried Precursor-Based Synthesis of Nanostructured Cobalt−Nickel Molybdates Co1-xNixMoO4

Abstract: A simple processing route to nanostructured mixed cobalt−nickel molybdates, Co1 - x Ni x MoO4 (0 ≤ x ≤ 1), has been developed. It is based on the use of precursors resulting from the freeze-drying of aqueous solutions of the appropriate common metal salts. Thermal decomposition of amorphous freeze-dried powders at low temperatures produces the nanostructured mixed oxides. A study of the influence of the preparative variables on the outcomes of this procedure is presented. The resulting materials have been cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…However, as can be seen in Figure 3f, both end-members had α- and β-phases corresponding to each material together. It is known that single-phase β-CoMoO 4 and α-NiMoO 4 can be formed by fast cooling and by slow cooling, respectively, to room temperature after post-annealing of their hydrates [14,17,18]. Meanwhile, D. Vie et al reported that the α-CoMoO 4 phase became detectable as a minority phase after heat treatment of the amorphous solid precursor at a temperature above 700°C [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as can be seen in Figure 3f, both end-members had α- and β-phases corresponding to each material together. It is known that single-phase β-CoMoO 4 and α-NiMoO 4 can be formed by fast cooling and by slow cooling, respectively, to room temperature after post-annealing of their hydrates [14,17,18]. Meanwhile, D. Vie et al reported that the α-CoMoO 4 phase became detectable as a minority phase after heat treatment of the amorphous solid precursor at a temperature above 700°C [17].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that single-phase β-CoMoO 4 and α-NiMoO 4 can be formed by fast cooling and by slow cooling, respectively, to room temperature after post-annealing of their hydrates [14,17,18]. Meanwhile, D. Vie et al reported that the α-CoMoO 4 phase became detectable as a minority phase after heat treatment of the amorphous solid precursor at a temperature above 700°C [17]. On the basis of these reports, we believe that the coexistence of α- and β-phases in CoMoO 4 and NiMoO 4 nanowires can be attributed to the medium cooling rate (≈10°C/min to 30°C/min) applied after post-annealing or to a change of phase transition temperature with the unique morphologies of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of its inherent interest, little attention has been paid in the literature on the use of nano sized oxide catalysts for ODH. The catalytic performance for the ODH of propane of the nano-sized molybdates of cobalt and nickel [13,14] has been compared to their homologues prepared by the conventional citrate method (to obtain similar surface areas). The freeze-drying method has been applied to obtain isomorphically substituted Co x Ni 1-x MoO 4 in the whole 0 B x B 1 range [14].…”
Section: Nanosized Oxide Catalysts For Odhmentioning
confidence: 99%
“…The catalytic performance for the ODH of propane of the nano-sized molybdates of cobalt and nickel [13,14] has been compared to their homologues prepared by the conventional citrate method (to obtain similar surface areas). The freeze-drying method has been applied to obtain isomorphically substituted Co x Ni 1-x MoO 4 in the whole 0 B x B 1 range [14]. Monophasic molybdates, with particle sizes \50 nm and BET specific areas 20-40 m 2 /g, were prepared from amorphous precursors obtained from mixed solutions of nitrates of Ni or Co and ammonium heptamolybdate, calcined at T C between 300 and 700°C.…”
Section: Nanosized Oxide Catalysts For Odhmentioning
confidence: 99%
“…Studies on the synthesis, characterization, and properties of nanoscale metal molybdates and tungstates, however, have comparably limited to date. Most often nanoscale molybdates and tungstates have been gained via simple water-based precipitation, [ 3 ] freeze-drying, [ 8 ] hydrothermal/solvothermal reactions, [ 9 ] thermal combustion, [ 10 ] or mechanochemical treatment. [ 11 ] Quite often the described materials were obtained with comparably large diameter (i.e., greater than 80 nm), and broad size distribution.…”
Section: Introductionmentioning
confidence: 99%